The Evolution of Food Deserts in a Small Midwestern City: The Case of Ypsilanti, Michigan: 1970 to 2010 - Semple, Hugh; Giguere, Andrew (Journal of planning education and research, 2018)
This study examines long-term geographic and demographic changes in food deserts in Ypsilanti, a small city of approximately 19,500 people located in Washtenaw County, Michigan. Because of the small size of Ypsilanti, it is sometimes difficult to imagine that food deserts can emerge in such urban settings and persist for decades. We argue that the persistence and geographic spread over time of food deserts in Ypsilanti are related to suburbanization, the decline of a once thriving auto-manufacturing sector, and changes in the structure of grocery retailing.